2015
DOI: 10.1167/iovs.14-15742
|View full text |Cite
|
Sign up to set email alerts
|

Peripapillary Choroidal Thickness in Young Asians With High Myopia

Abstract: Highly myopic eyes have significantly thinner peripapillary choroid and showed different distribution of thickness, compared with emmetropes. Axial length, IOP, and presence of posterior staphyloma and chorioretinal atrophy significantly influence PPCT and should be taken into consideration during clinical interpretation of PPCT measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
42
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 30 publications
9
42
2
1
Order By: Relevance
“…24,31 Relationship between SE and PPCT is more reliable in our study than previous results, as children with different refractive status and different degree of myopia were included in the study and the sample size was large. The relationship between age and PPCT is also disputed, as the current study and some previous studies showed no significant correlations, 20,22,26,31 while some other studies indicated a negative correlation between the two parameters. 24,28 The mean age of the participants may influence this relationship, as results from children and young adults showed no significant correlations.…”
Section: Independent Factors Of Cht Throughout the Posterior Polecontrasting
confidence: 82%
See 3 more Smart Citations
“…24,31 Relationship between SE and PPCT is more reliable in our study than previous results, as children with different refractive status and different degree of myopia were included in the study and the sample size was large. The relationship between age and PPCT is also disputed, as the current study and some previous studies showed no significant correlations, 20,22,26,31 while some other studies indicated a negative correlation between the two parameters. 24,28 The mean age of the participants may influence this relationship, as results from children and young adults showed no significant correlations.…”
Section: Independent Factors Of Cht Throughout the Posterior Polecontrasting
confidence: 82%
“…This may suggest an uneven expansion of the fundus in the peripapillary region during the early stage of myopia, as expansion of the fundus may lead to choroidal thinning and atrophy. Additionally, some previous studies have found there to be a negative correlation between AL and PPCT either partially or globally, [20][21][22]28 while other studies reported that neither the SE nor the AL was independently associated with PPCT. 24,31 Relationship between SE and PPCT is more reliable in our study than previous results, as children with different refractive status and different degree of myopia were included in the study and the sample size was large.…”
Section: Independent Factors Of Cht Throughout the Posterior Polementioning
confidence: 98%
See 2 more Smart Citations
“…6 A significant thinning in CT related with myopia was observed and CT in myopia had negative correlation with refractive power, axial length, and age, which was mentioned in previous studies (Table 3). 5,6,16,18,19 Excimer laser refractive surgery is a common option for correcting myopia. Our study, first reported that the choroid becomes thicker following myopic refractive surgery.…”
Section: Discussionmentioning
confidence: 99%